Portfolio diversification utilising rolling economic drawdown constraints and risk factor analysis - Mills, Bradley (Department of Finance and Tax, 2019)
This study investigates a new asset allocation technique termed Factor Adjusted Rolling Economic Drawdown (FAREDD), whereby resources are allocated to different assets by way of integrating Principle Component Analysis (PCA) with existing Rolling Economic Drawdown Methods (REDD). The primary purpose of this model is to create a portfolio with low drawdown levels, that can withstand turbulent market periods thus protecting portfolio value through providing stronger diversification benefits while still seeking to maximise risk adjusted and overall return. This will have strong implications for investors as it could provide an additional method and tool to be considered during the asset allocation decision stage if they have a strong drawdown aversion. The concept of FAREDD is developed in this study within a South African context and compares this method with several traditional allocation methods including mean-variance optimised models, risk parity as well as traditional rolling economic drawdown models. So far, at the point of writing this study, the author has been unable to find any previous studies documenting this type of application of PCA to REDD. In addition to this, all previous studies that has investigated rolling economic drawdown has been conducted exclusively on the United States of America. The literature finds that REDD provides a viable and superior alternative to traditional asset allocation in the long run. Thus, as part of this study, a second objective is to investigate whether REDD models provide sufficient protection and superior returns in a developing economy with a significantly lower number of available liquid assets and higher volatility due to increased political, economic and business risk, when compared to alternative more traditional allocation techniques. The key findings of this study are that the FAREDD model does outperform the traditional REDD model that it is compared to for the period and it also meets the objective of providing low drawdowns and volatility while achieving strong risk-adjusted returns. However, the model does not provide the strongest drawdown protection of all portfolios tested. The FAREDD model is surpassed by the minimum-variance portfolio in this regard but from a risk adjusted basis and an overall return perspective it far outperforms the minimum-variance portfolio. Therefore, the performance of the FAREDD model is mixed and its optimality would need to be assessed relative to an investor’s risk appetite and risk-return trade-off. In addition to this, the paper finds that the performance of traditional REDD models in the South African context are mixed when compared to traditional asset allocation techniques thereby indicating that REDD models may not be superior in the South African market place at all times. However, they can provide relevant and potential asset allocation alternatives for mangers to consider.